Trường hợp 1: \(x\ge2\)
Ta có: \(\left|x-1\right|+\left|2-x\right|=\left(x-1\right)-\left(2-x\right)\)\(=2x-3\)
Vì \(x\ge2\Rightarrow2x\ge4\Rightarrow2x-3\ge1\)
Vậy \(\left|x-1\right|+\left|2-x\right|\ge1\)( khi \(x\ge2\))
Trường hợp 2: \(1\le x\le2\)
Ta có: \(\left|x-1\right|+\left|2-x\right|=x-1+2-x=1\)( luôn luôn đúng )
Trường hợp 3: \(x< 1\)
Ta có: \(\left|x-1\right|+\left|2-x\right|\)\(=-\left(x-1\right)+\left(2-x\right)=3-2x\)
Vì \(x< 1\Rightarrow-2x>-2\Rightarrow3-2x\ge3-2=1\)
Vậy \(\left|x-1\right|+\left|2-x\right|\ge1\)( Với mọi \(x\in R\))